2013
DOI: 10.1038/ncomms3232
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary structural elements determine the extent and specificity of messenger RNA editing

Abstract: The specificity and extent of RNA editing by ADAR enzymes is determined largely by local primary sequence and secondary structural imperfections in duplex RNA. Here we surgically alter conserved cis elements associated with a cluster of ADAR modification sites within the endogenous Drosophila paralytic transcript. In addition to the local requirement for a central imperfect RNA duplex containing the modified adenosines, we demonstrate that a secondary RNA duplex containing splicing signals strongly modulates R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 59 publications
4
64
0
1
Order By: Relevance
“…In the Drosophila editing target para, dsRNA elements, including a predicted pseudoknot, created by the intron downstream from exonic editing sites, influence editing efficiency even though these regions lack editing sites (Rieder et al 2013). Similarly, downstream dsRNA hairpins within the introns of the human Gabra-3 and Neil1 transcripts have also been shown to increase editing efficiency of adjacent editing sites in coding regions (Daniel et al 2012(Daniel et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In the Drosophila editing target para, dsRNA elements, including a predicted pseudoknot, created by the intron downstream from exonic editing sites, influence editing efficiency even though these regions lack editing sites (Rieder et al 2013). Similarly, downstream dsRNA hairpins within the introns of the human Gabra-3 and Neil1 transcripts have also been shown to increase editing efficiency of adjacent editing sites in coding regions (Daniel et al 2012(Daniel et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Because ADAR proteins recognize double-stranded RNAs (dsRNAs), substitution of adenosines by inosines may alter the stability of the RNA structures and influence the accessibility of splice sites (Morse et al 2002;Blow et al 2004;Levanon et al 2004;Mazloomian and Meyer 2015). In general, ADAR and splicing machineries may act on the same dsRNA substrates, leading to the interplay between these two processes (Reenan et al 2000;Rieder et al 2013). However, structure-mediated splicing modulation by RNA editing or ADAR binding is relatively poorly understood.…”
mentioning
confidence: 99%
“…Consistent with this idea, recent work in Drosophila has demonstrated that editing events located in close proximity (»10 nucleotides apart) are not functionally coupled and require binding of ADARs to 2 distinct locations on the dsRNA structure. 56 Furthermore, early biochemical work supports the hypothesis of re-binding and editing by ADARs, as partially edited RNAs re-introduced to ADARs in vitro were capable of undergoing further deamination. 23 In addition to the pair-wise editing events, the correlation analysis between the overall co-occurrence of 2 adenosines, revealed that distant editing events separated by multiple helical turns, such as nucleotides 95 and 178 in syntaxin, were positively correlated (dice coefficient of 0.05).…”
Section: Discussionmentioning
confidence: 90%